An Evaluation and Impact Assessment of Business Incubation Models in Eastern Europe and Central Asia - World Bank (2015)
A business incubator can play an important role in developing and supporting startup companies, and has the potential to stimulate local and regional economies. Incubation is a continuous relationship between the incubator and the early-stage entrepreneur, with graduation as the target and occurring when the early-stage company has reached sufficient maturity. Through the incubation process, the support provided by the incubator evolves along with the development needs of the business. Business incubation can be a valuable tool for stimulating the startup and growth of new enterprises. Successful incubators accelerate the growth of the clients' businesses as compared to new or small businesses operating independently. This assessment aims to provide further insights on the outcomes of business incubation for the enterprises directly served by the incubators, as well as for the broader socio-economic environment the business incubators operate in. This study assesses nine business incubators in eight countries across the Eastern Europe and Central Asia (ECA) region, namely Armenia, Belarus, Kazakhstan, Poland, Romania, the Russian Federation, Serbia, and Turkey. These countries were selected to obtain representation from the various sub-regions of ECA. The study concludes that the incubators studied have generally been effective in fostering entrepreneurship and innovation in their local contexts.